Bile acid changes after metabolic surgery are linked to improvement in insulin sensitivity. Issue 9 (19th June 2019) - Ahlin, S; Cefalo, C; Bondia-Pons, I; Capristo, E; Marini, L; Gastaldelli, A; Mingrone, G; Nolan, J J
Abstract: Background: Metabolic surgery is associated with a prompt improvement in insulin resistance, although the mechanism of action remains unknown. The literature on bile acid changes after metabolic surgery is conflicting, and insulin sensitivity is generally assessed by indirect methods. The aim of this study was to investigate the relationship between improvement in insulin sensitivity and concentration of circulating bile acids after biliopancreatic diversion (BPD) and Roux-en-Y gastric bypass (RYGB). Methods: This was a prospective observational study of nine patients who underwent BPD and six who had RYGB. Inclusion criteria for participation were a BMI in excess of 40 kg/m 2, no previous diagnosis of type 2 diabetes and willingness to participate. Exclusion criteria were major endocrine diseases, malignancies and liver cirrhosis. Follow-up visits were carried out after a mean(s.d.) of 185·3(72·9) days. Fasting plasma bile acids were assessed by ultra-high-performance liquid chromatography coupled with a triple quadrupole mass spectrometer, and insulin sensitivity was measured by means of a hyperinsulinaemic–euglycaemic clamp. Results: A significant increase in all bile acids, as well as an amelioration of insulin sensitivity, was observed after metabolic surgery. An increase in conjugated secondary bile acids was significantly associated with an increase in insulin sensitivity. Only the increase in glycodeoxycholic acid was significantly associated with an increase in insulin sensitivity in analysis of individual conjugated secondary bile acids. Conclusion: Glycodeoxycholic acid might drive the improved insulin sensitivity after metabolic surgery. Graphical Abstract: The results of this study show that plasma levels of total bile acids are markedly increased and to a similar extent after both biliopancreatic diversion and Roux-en-Y gastric bypass surgery, alongside a marked improvement in insulin sensitivity. In addition, the increases in secondary conjugated bile acids, in particular glycodeoxycholic acid, are closely associated with, and can predict, the improvement in insulin sensitivity after metabolic surgery. Metabolic confirmation